PENGARUH PANIC BUYING TERHADAP KEPUTUSAN PEMBELIAN - Faatikah, Thufailah Cintantya; Yuniarinto, Agung (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
Consumers’ purchase decision in response to the Covid-19 pandemic, in which they buy goods in remarkably large quantities due to perceived scarcity, is called panic buying. The objective of this quantitative research is to identify and analyse the effect of perception, fear of the unknown, coping behaviour, and social psychology on purchase decisions made in Indomaret convenience stores or minimarkets in Malang. The samples are 151 people with the minimum age of 17 years who have made any purchase at Indomaret outlets in Malang. The results of the multiple linear regression analysis indicate that fear of the unknown, coping behaviour, and social psychology significantly influence the purchase decision made in Indomaret convenience stores in Malang, while the effect of perception is insignificant. This means that consumer’s decision to make purchases at Indomaret outlets is determined by fear of the unknown, coping behaviour, and social psychology. Therefore, Indomaret convenience stores in Malang need to increase the effect from aspects that are directly seen by their customers.